Preparation and property testing of compatibilized poly(l -lactide)/thermoplastic polyurethane blends - Kanyarat Suthapakti (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Poly(l-lactide) (PLL) has been blended with a polycaprolactone-based thermoplastic polyurethane (TPU) elastomer as a toughening agent and a poly(l-lactide-co-caprolactone) (PLLCL) copolymer as a compatibilizer. Both 2-component (PLL/TPU) and 3-component (PLL/TPU/PLLCL) blends were prepared by melt mixing, characterized, hot-pressed into thin sheets and their tensile properties tested. The results showed that, although the TPU could toughen the PLL, the blends were largely immiscible leading to phase separation. However, addition of the PLLCL copolymer improved blend compatibility. The best all-round properties were found for the 3-component blend of composition PLL/TPU/PLLCL = 90/10/10 parts by weight.